Overexpression of inosine 5′-monophosphate dehydrogenase type II mediates chemoresistance to human osteosarcoma cells - Fellenberg, Jörg; Kunz, Pierre; Sähr, Heiner; Depeweg, Daniela (PLOS ONE, 2010)
Background Chemoresistance is the principal reason for poor survival and disease recurrence in osteosarcoma patients. Inosine 5′-monophosphate dehydrogenase type II (IMPDH2) encodes the rate-limiting enzyme in the de novo guanine nucleotide biosynthesis and has been linked to cell growth, differentiation, and malignant transformation. In a previous study we identified IMPDH2 as an independent prognostic factor and observed frequent IMPDH2 overexpression in osteosarcoma patients with poor response to chemotherapy. The aim of this study was to provide evidence for direct involvement of IMPDH2 in the development of chemoresistance. Methodology/Principal Findings Stable cell lines overexpressing IMPDH2 and IMPDH2 knock-down cells were generated using the osteosarcoma cell line Saos-2 as parental cell line. Chemosensitivity, proliferation, and the expression of apoptosis-related proteins were analyzed by flow cytometry, WST-1-assay, and western blot analysis. Overexpression of IMPDH2 in Saos-2 cells induced strong chemoresistance against cisplatin and methotrexate. The observed chemoresistance was mediated at least in part by increased expression of the anti-apoptotic proteins Bcl-2, Mcl-1, and XIAP, reduced activation of caspase-9, and, consequently, reduced cleavage of the caspase substrate PARP. Pharmacological inhibition of IMPDH induced a moderate reduction of cell viability and a strong decrease of cell proliferation, but no increase in chemosensitivity. However, chemoresistant IMPDH2-overexpressing cells could be resensitized by RNA interference-mediated downregulation of IMPDH2. Conclusions IMPDH2 is directly involved in the development of chemoresistance in osteosarcoma cells, suggesting that targeting of IMPDH2 by RNAi or more effective pharmacological inhibitors in combination with chemotherapy might be a promising means of overcoming chemoresistance in osteosarcomas with high IMPDH2 expression.
Gesehen am 27.02.2023